Immunohistochemical Analysis of Expressions of RB1, CDK4, HSP90, cPLA2G4A, and CHMP2B Is Helpful in Distinction between Myxofibrosarcoma and Myxoid Liposarcoma. (October 2014) - Wang, Tao; Goodman, Mark A.; McGough, Richard L.; Weiss, Kurt R.; Rao, Uma N. M.
The role and diagnostic efficacy of gene and protein products RB1, CDK4, CHMP2B, HSP90, and cPLA2G4A, all previously shown to be involved in tumor genesis and cell proliferation, were examined by immunohistochemical techniques in 32 cases of myxofibrosarcomas and 29 myxoid liposarcomas (all diagnosis had been confirmed by fluorescence in situ hybridization). HSP90 demonstrated strong nuclear and cytoplasmic positivity in all myxoid liposarcoma cases, while only 4 myxofibrosarcomas showed scattered HSP90 positivity. All but 4 cases of myxofibrosarcoma displayed strong positivity for cPLA2G4A, while only 2 myxoid liposarcoma cases were cPLA2G4A positive and both were CHMP2B negative. Overexpression of both cPLA2G4A and CHMP2B also suggested higher tumor grade. In conclusion, HSP90 and cPLA2G4A immunohistochemical stains are useful markers to distinguish myxofibrosarcoma from myxoid liposarcoma.